Critical survey of poetry [ American poets - Reisman, Rosemary M. Canfield; Gale Group (Pasadena, California : Salem Pres, 2011)
Profiles major poets throughout history and the world, including analyses of their significant individual poems or collections. This subset focuses on American poets.
v. 1. Diane Ackerman-Edward Field -- v. 2. Roland Flint-Wing Tek Lum -- v. 3. Michael McClure-Dave Smith -- v. 4. William Jay Smith-Louis Zukofsky, resources, indexes.
Includes bibliographical references and indexes
Keywords: Poetry -- Bio-bibliography; Poetry -- History and criticism -- Dictionaries; Poets, American -- Biography -- Dictionaries